Mind the Gap! ECN+ Directive Proposal on its Way to Eliminate Deficiencies of Regulation 1/2003: Polish Perspective - Agata Jurkowska-Gomułka (Market and Competition Law Review)
This article aims at answering the question whether the Commission’s proposal intended to empower Member States’ competition authorities to be more effective enforcers (ECN+ Directive) actually brings effective solutions to all weaknesses of Regulation 1/2003, which influenced an inefficient application of Articles 101 and 102 TFEU in some Member States (among them Poland, which will be taken as a point of reference). The first part of the article constitutes a review upon the application of Regulation 1/2003 in Poland. Interestingly, the beginning of its enforcement coincides with the total period of application of EU law in Poland, since the country joined the EU on the same day the Regulation entered into force. The problem with Regulation 1/2003 is that it does not seem to enhance the enforcement of the Community’s competition rules by national enforcers, including NCAs and courts. The reason for this failure lies inter alia in the deficiencies of the principles adopted in the Regulation itself, including a lack of procedural unification (or at least some harmonisation) in cases where European substantive law is to be applied. In the second part of the article, the content of the Commission’s proposal on ECN+ Directive is analysed in order to find whether new regulations are able to solve problems identified in the Polish application of the Treaty’s provisions. The article concludes with an overall assessment of the proposed Directive and a list of conditions for effective implementation of the Directive.